SHUTDOWN PLANNING ON WEST NATUNA TRANSPORTATION SYSTEM (WNTS) OFFSHORE PIPELINE NETWORK BY THE LINEPACK - Giovanni, Irsyad
Gas and oil have differences when they are produced. Gas needs to be directly processed and transported to the buyer. In the process of gas production, sometimes there are some technical problems that are experienced by suppliers in order that the process of transporting gas to the buyer is not in accordance with the contract agreement that has been enforced both in terms of gas quantity and quality. The linepack phenomenon can be utilized in a production flow rate design strategy by utilizing the compressible gas properties and the pipe itself as a gas storage. The case study was implemented on the WNTS gas pipeline network. The WNTS pipeline network is the pipeline system 656 km long under the sea that connects gas transportation from various suppliers who produce gas in the Natuna Sea region to buyers in Singapore. The dynamic field conditions make it possible for anything to happen during production operations, such as an unplanned shutdown or planned shutdown from one of the suppliers which causes gas delivery from that supplier to stop so that the gas sent to the buyer through the pipeline is less than the gas sales contract agreement so a solution is needed if this happens. Dynamic simulations on WNTS gas transportation was carried out including calculations of the linepack phenomenon in the gas pipeline network as a reference for production forecasting and selection of appropriate scenario optimization when a planned shutdown occurs at one of the suppliers. Next, a shutdown scenario for each supplier is simulated along with the calculation of gas allocation and engineering of the flow rate of gas delivery to the delivery point with the result that the difference of linepack calculation in the scenario is less than 1% compared to the linepack calculation during normal operating conditions so that the need for gas supply is still can be maintained even though there is a shutdown at one of its suppliers.